Penyiram Air Otomatis Kumbung Jamur Tiram Pada Pesantren Ma. Mambaul ‘Ulum, Bengkulu Tengah - Qurratun nisa, Laura shafa (Jurnal Inovasi Pengabdian Masyarakat Pendidikan, 2023)
Pondok Pesantren MA. Mambaul 'Ulum, which is located in Bengkulu Tengah Regency, Bengkulu Province, has an oyster mushroom business unit to support the operational needs of the school. Maintenance, especially baglog watering on oyster mushroom house, is carried out conventionally. Through service activities, a baglog sprinkler automation system was built that works based on humidity and temperature in the mushroom house. The system utilizes electrical energy sourced from solar panels that are integrated with an automatic sprinkler system. The method used in the target audience of service (teachers and students) starts from the initial coordination, then the delivery of the material in theory and practice, followed by the installation of the system as a whole and running and testing the system. Based on the test results, it was obtained that the system can run properly according to the conditions set on the automated system. The watering automatic system active while the oyster mushroom house in non-ideal environmental condition.